A review on phytochemical and pharmacological values of Aegle marmelos - Lomate, Krushna A.; Murthy, Krishna; Adak, Vishal S.; Shete, Rajkumar V. V. (Journal of Drug Delivery and Therapeutics, 2021)
India is the largest producer of medicinal plants and is rightly referred to as "the World’s Botanical Garden." Medicinal plants play a key role in the health and vitality of humans and animals alike. Researchers have been attempting to recognize and validate plant-derived substances for the treatment of various diseases that promote compounds for health and nutrition for the past few years. Bael is a common plant that originated in India (Aegle marmelos). According to a study of the literature, entire parts of the plant, such as roots, barks, leaves, fruits, seeds, and flowers, are used to treat various diseases. Bangladesh, Indonesia, China, and other Asian countries, for example, it is a spiritual, religious, and medicinal plant that can be found all over the world. It has a number of therapeutic applications. Nowadays, various products from various parts of the plant are prepared. The biological profile, botanical description, physicochemical parameters, conventional uses, therapeutic applications and creative aspects are included in this study. The purpose of the present analysis is to compile the general chemical profile, both medicinal and economic value, value-added items such as juice, jam and toffee, and other uses of Aegle marmelos. Keywords: Aegle marmelos, Rutaceae, Medicinal Values